Towards sustainable development: a study of the economic and environmental convergence of china's transformation economy - Marwa Sami Ahmed; Ibrahim Khaleel Ibrahim; Ahmed Kalel Hasan Alzarkany; Morklyanyk Bohdan (Encuentros)
The shift of China towards a sustainable economic model represents a substantial transformation in the worldwide scenario. It entails the integration of economic growth with environmental stewardship.The article investigates the intersection of economic and environmental factors in China's changing economy, focusing on the country's efforts to balance rapid economic growth with ecological sustainability.  This study employs a comprehensive examination of several data sources, including pollution reduction statistics, the implementation of environmentally friendly technology, and the formation of a circular economy, to provide a detailed evaluation of China's progress in attaining sustainable development. Preliminary statistics indicate significant advancements in achieving economic and environmental congruity in China. The nation's commitment to decreasing pollution levels, improving sustainable technology, and fostering a circular economy model has led to positive outcomes. However, challenges must be addressed to include these features and accomplish sustainable development goals fully.